2012
DOI: 10.1890/es12-00203.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance towards generalist herbivory in the new range of a habitat‐forming seaweed

Abstract: Abstract. Interactions between plants and their biotic environment can drastically change during rangeexpansion and result in rapid adaptive evolution of plant traits. According to the influential evolution of increased competitive ability (EICA) hypothesis escape from specialist natural enemies will lead to a reduction in defense levels, but the way in which generalist consumers in the new ranges affect the evolution of plant defenses remains poorly understood. We conducted a four month controlled environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
(87 reference statements)
1
17
1
Order By: Relevance
“…Although phlorotannins are found in many fucoids, the abundances observed in S. muticum were particularly high; comparable to those found in the highly grazer-resistant Ascophyllum nodosum Kurr & Davies, 2017b). Pronounced invasion success has been attributed to chemical defences in other species of algae (Forslund et al, 2010;Enge et al, 2012;Nylund et al, 2012;Svensson et al, 2013) and plants (Van Kleunen & Schmid, 2003;Leger & Forister, 2005;Huang et al, 2010;Lind & Parker, 2010), and may also explain the success of S. muticum outside of its native range (Engelen et al, 2015). Although a large body of evidence suggests that a high diversity of native plants often affords better resistance to invasions by controphics (see Theoharides & Dukes, 2007), surprisingly few studies have investigated the diversity of native enemies on the topdown-pressure experienced by invasive species (Maron & Vilá, 2001;Agrawal & Kotanen, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…Although phlorotannins are found in many fucoids, the abundances observed in S. muticum were particularly high; comparable to those found in the highly grazer-resistant Ascophyllum nodosum Kurr & Davies, 2017b). Pronounced invasion success has been attributed to chemical defences in other species of algae (Forslund et al, 2010;Enge et al, 2012;Nylund et al, 2012;Svensson et al, 2013) and plants (Van Kleunen & Schmid, 2003;Leger & Forister, 2005;Huang et al, 2010;Lind & Parker, 2010), and may also explain the success of S. muticum outside of its native range (Engelen et al, 2015). Although a large body of evidence suggests that a high diversity of native plants often affords better resistance to invasions by controphics (see Theoharides & Dukes, 2007), surprisingly few studies have investigated the diversity of native enemies on the topdown-pressure experienced by invasive species (Maron & Vilá, 2001;Agrawal & Kotanen, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…In range expanding algae, resistance towards generalist herbivores was lower in core populations to populations in the extended range (Nylund et al 2012). In contrast, resistance against a generalist caterpillar was higher in core populations of the range expanding plant Bunias orientalis (Fortuna et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The overlapping habitat ranges of Idotea spp. and F. vesiculosus have forced a selection for high grazing-resistance in F. vesiculosus during colonization of the BS (Nylund et al ., 2012). This seems not to be the case for F. radicans .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of serious changes in nutrient load, oxygen concentration, SSS and SST predicted for the Baltic Proper, and a northern/north-eastern shift of species, may result in genetic separation of local populations. Phylogeographical studies have indicated that Baltic populations in general (Johannesson & Andr e, 2006), and populations of Idotea spp., F. vesiculosus and G. aculeatus in particular, have lost genetic variation in contrast to populations from the Atlantic (Tatarenkov et al, 2007;Nylund et al, 2012;DeFaveri et al, 2013;Leidenberger, 2013). A large population size with a high level of genetic variation can increase the capacity to adapt to environmental changes, in comparison with small isolated populations with low genetic diversity (Johannesson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation